Motion behavior of a high-current fault electric arc occurred in the dead zone of protection in a substation - Teng, Jun; Zhang, Yongjie; Chen, Danhua; Sheng, Ji; Wang, Shuaijie; Huang, Wei (Frontiers in Energy Research, 2024)
Since the dead-zone fault in substations often has a relatively long removal time, it may damage the insulation of power equipment and even threaten the stability of the power system. In this paper, the movement of the dead-zone fault electric arc in a 220-kV substation is investigated. The arc chain model for the dead-zone fault electric arc is developed; the influences of electromagnetic force, thermal buoyancy, and the air resistance stressed on the electric arc are comprehensively considered. The electric arc velocity and displacement are computed. Then, the spreading characteristics of the dead-zone electric arc under various conditions are studied. The spreading trend of the dead-zone fault electric arc is summarized. Finally, measures to inhibit the spreading of the electric arc are suggested. The study indicates that the movement of the electric arc in the dead zone during the early stage is primarily influenced by the electromagnetic force resulting from the overpass and conductor, and the arc is concave and has an irregular trajectory. The inclination angle of the conductor significantly affects the direction of the electromagnetic force. If the conductor is laid horizontally, the electric arc is subjected to a smaller force. The electromagnetic force stressed on the electric arc is mainly attributed to the fault phase conductor and the electric arc body itself, whereas those from the other phase conductors are minor. The initial position of the arc root has a certain impact on the movement of the electric arc. The use of the insulating materials restricts the arc root movement.